The Effect of Taxpayer Perceptions of the Effectiveness of the Implementation of Government Regulation of the Republic of Indonesia Number 58 of 2023 on Individual Taxpayer Compliance in Reporting Tax Return with Understanding of Taxation as a Moderating - Wulandari, Novita; Din, Muhammad; Parwati, Ni Made Suwitri; Tanra, Andi Ainil Mufidah (International Journal of Science and Society, 2024)
This research endeavors to evaluate the impact of taxpayer perceptions on the efficacy of the implementation of Government Regulation of the Republic of Indonesia Number of 2023 in enhancing the compliance of individual taxpayers in filing annual tax returns, with tax comprehension serving as a moderating variable. The study included 169,672 individual taxpayers who were registered at KPP Pratama Palu. The research sample was randomly selected using a random sampling approach, and the total number of samples used was 399 respondents, as determined by the Slovin formula. This study employs a quantitative methodology, utilizing questionnaires distributed directly and online. The WarpPLS 7.0 software used the Partial Least Squares (PLS) method to analyze the data. The findings indicated that taxpayers' assessments of the efficacy of Government Regulation of the Republic of Indonesia Number of 2023 substantially impacted their compliance with tax return reporting, as evidenced by a path coefficient value of 0.516 and a p-value of less than 0.001. Furthermore, the relationship between perception and compliance is fortified by tax understanding as a moderating variable, as evidenced by a path coefficient value of 0.097 and a p-value of 0.026.